Stepan Bandera : the life and afterlife of a Ukrainian nationalist : fascism, genocide, and cult - Rossolinski, Grzegorz (Ibidem-Verlag, 2014)
The Life and Afterlife of a Ukrainian Nationalist is the first comprehensive and scholarly biography of the Ukrainian far-right leader Stepan Bandera and the first in-depth study of his political cult. In this fascinating book, Grzegorz Rossolinski-Liebe illuminates the life of a mythologized personality and scrutinizes the history of the most violent twentieth-century Ukrainian nationalist movement: the Organization of Ukrainian Nationalists and its Ukrainian Insurgent Army.Elucidating the circumstances in which Bandera and his movement emerged and functioned, Rossolinski-Liebe explains how f.